2011
DOI: 10.1002/pat.2022
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in gas separation properties of a polymeric membrane through the incorporation of inorganic nano‐particles

Abstract: The present work tries to introduce a high‐performance nano‐composite membrane by using polydimethylsiloxane (PDMS) as its main polymer matrix to meet some specific requirements in industrial gas separations. Different nano‐composite membranes were synthesized by incorporating various amounts of nano‐sized silica particles into the PDMS matrix. A uniform dispersion of nano‐particles in the host membranes was obtained. The nano‐composite membranes were characterized morphologically by scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…The findings of current study (results permeability), as shown in Fig. 8, are in an excellent consistent with those of Merkel et al [45], Raharjo et al [46], Prabhakar et al [47], Stern et al [48] and our previous study [33,44]. Robeson in 1991 [49] introduced a trade-off between gas permeabilities and selectivities of polymeric membranes known as the "upper-bound trade-off" curves [50], as shown in Fig.…”
Section: Linear Pressure Relation Of Permeabilitysupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of current study (results permeability), as shown in Fig. 8, are in an excellent consistent with those of Merkel et al [45], Raharjo et al [46], Prabhakar et al [47], Stern et al [48] and our previous study [33,44]. Robeson in 1991 [49] introduced a trade-off between gas permeabilities and selectivities of polymeric membranes known as the "upper-bound trade-off" curves [50], as shown in Fig.…”
Section: Linear Pressure Relation Of Permeabilitysupporting
confidence: 93%
“…It could be observed from the gas permeation results that the pore size closest to the kinetic diameter of permeating molecules to be separated is overally ineffective in improving selectivity of the rubbery PDMS membranes. It was expected that the PDMS/5A MMM is the best membrane among the others for CO 2 (3.3 Å )/ CH 4 (3.8 Å ) separation whereas this results in a very little enhanced selectivity and a declined permeability despite its pore size (4.3 Å ) which is large enough to fit the kinetic diameters of gas molecules and to be the most suitable membrane with desired properties among the zeolites investigated for CO 2 [48] and our previous study [33,44].…”
Section: 6mentioning
confidence: 95%
See 1 more Smart Citation
“…zeolites, metal–organic frameworks (MOFs) and carbon nanotubes (CNTs)) and non‐porous (e.g. metal oxide) materials 13–16 . Although the embodiment of well‐optimized nanoparticles loading into MMMs can generally boost CO 2 permeability across the membranes, different CO 2 /CH 4 selectivity results have been reported by the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric membranes are still one of the most common types of membrane used for gas separation, in which the transport takes place according to a solution-diffusion mechanism [25]. Hence, they either need to be fully dense or asymmetric, whereas the separation process happens due to the different affinities between the selective layer and gases [26].…”
Section: Introductionmentioning
confidence: 99%